Anaxagoras and the Development of the Sorites Paradox - Weiss, Yale (Phronesis, 2026)
Most contemporary scholars attribute the first formulation of the Sorites paradox to Eubulides. However, Sextus (DK 59B21) attributes strikingly soritical reasoning to Anaxagoras in arguing for the unreliability of the senses. In this article, I present and evaluate evidence for two theses, a stronger and a weaker. The strong thesis is that Anaxagoras formulated something recognizable as the Sorites paradox in arguing for the unreliability of the senses, and the weak thesis is that Anaxagoras importantly anticipated the Sorites paradox. I argue that either thesis can help illuminate certain puzzling aspects of the development of the Sorites paradox in antiquity.